Crisis and conflict: Soweto 1976-1977 - Moss, Glenn (My University, 1982)
This dissertation examines two themes that emerged from the most intense periods of conflict in the Soweto crisis of 1976: these are the clashes between hostel dwellers and other township residents during August 1976; and the stay-away campaigns called by the Soweto Students' Representative Council between August and November 1976. The conflicts which emerged between hostel inmates and other township residents were indicative of a serious rift between these two township groups. These already-existing antagonisms were made worse by the intervention of the police, Inkatha and Soweto Urban Bantu Council members who planned to mobilize the hostel men as a strike breakers in the stay-away of 23 - 25 August 1976. In addition to this, the level of tension was heightened by harassment which hostel inmates suffered from other township residents - especially the youth - when they ignored the stay-away call. Although these factors played a role in provoking the violent response of the hostel men, the nature of the hostels themselves was a more important causal factor. The reproduction of a section of the African working class separately from the rest of the township community, via the institution of hostels, created the material conditions for an antagonistic relationship to develop between hostel men and other township residents. The Soweto stay-away campaigns of August - November 1976 represented the pinnacle of the student-led resistance. However, the stay-away as a weapon of struggle differs markedly from the mass strike, which it is often equated with. The stay-away campaigns were more limited than a mass strike, and accordingly must be subject to a different basis of assessment. The stay-aways features of protest demonstrations rather than mass strikes. After demonstrations, they must be assessed as tactical failures. This is not because they failed to achieve the demands which formed part of the demonstrations, for this is not a basis for evaluating demonstration activity. They failed because they were unable to create conditions for more advanced and mature conditions of political struggle. There was no deepening and extension of the organization as a result of the stay-away campaigns; and .although workers from Soweto participated in these demonstrative actions, this was not as a class. As such, working-class interests were not strengthened in relation to other classes, fractions, and strata within the township.
A Dissertation Submitted to the Faculty of Arts, University of Witwatersrand, Johannesburg, for the Degree of Master of Art
Keywords: Crisis-Soweto; Conflict-Soweto